2015
DOI: 10.1016/j.imlet.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Secreted aspartic protease 2 of Candida albicans inactivates factor H and the macrophage factor H-receptors CR3 (CD11b/CD18) and CR4 (CD11c/CD18)

Abstract: The opportunistic pathogenic yeast Candida albicans employs several mechanisms to interfere with the human complement system. This includes the acquisition of host complement regulators, the release of molecules that scavenge complement proteins or block cellular receptors, and the secretion of proteases that inactivate complement components. Furthermore, FH enhanced zymosan-induced production of these cytokines. C. albicans Sap2 cleaved FH, diminishing its complement regulatory activity, and Sap2-treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…An additional way for pathogens to escape complement attack is by recruiting (i.e., hijacking ) complement inhibitors from the host, such as FH (and C4BP) [128130]. Indeed, some pathogens mimic a host surface by capturing these soluble complement regulators or, alternatively, target and inactivate complement inhibitors with secreted proteins/proteases [48, 131]; once a given pathogen has recruited complement inhibitors on to its own surface, it is likely protected from the complement attack as if it were self . There are several examples of bacteria that can acquire FH via the presentation of specific binding proteins.…”
Section: Factor H and Immune Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional way for pathogens to escape complement attack is by recruiting (i.e., hijacking ) complement inhibitors from the host, such as FH (and C4BP) [128130]. Indeed, some pathogens mimic a host surface by capturing these soluble complement regulators or, alternatively, target and inactivate complement inhibitors with secreted proteins/proteases [48, 131]; once a given pathogen has recruited complement inhibitors on to its own surface, it is likely protected from the complement attack as if it were self . There are several examples of bacteria that can acquire FH via the presentation of specific binding proteins.…”
Section: Factor H and Immune Evasionmentioning
confidence: 99%
“…As noted above, some pathogens can escape the immune response by synthesizing and secreting soluble proteases that can target selected complement components. This is the case for Candida albicans whose aspartic protease 2 inactivates FH and the macrophage FH-receptors CR3 and CR4 [131]. In this context, it appears that the selective degradation of FH by the microbe-encoded protease helps circumvent the pro-phagocytic activity of FH (see above).…”
Section: Factor H and Immune Evasionmentioning
confidence: 99%
“…This appears counterproductive because cleaved FH then loses its ability to inhibit complement activation (51). However, microbes may gain advantage from a more inflammatory micro-environment (53, 54) or, because their proteases could also cleave complement factors necessary for the propagation of the cascade (55), the functional inactivation of FH may not cause significant disadvantage in complement resistance.…”
Section: Role Of Fh In Host–microbe Interactionsmentioning
confidence: 99%
“…In this non-canonical role, FH was described to act as a bridging molecule between complement receptor 3 (CR3; CD11b/CD18) and pathogens, and helping either pathogen entry into host cells or the antimicrobial response of the host cells (51, 5862). Such scenarios were described for FH bound to S. pneumoniae, N. gonorrhoeae , and Candida albicans (5861).…”
Section: Role Of Fh In Host–microbe Interactionsmentioning
confidence: 99%
“…It has been recently shown that both CR3 and CR4 function as FH receptors on monocyte-derived macrophages (28). Thus, we exposed monocytes to blocking mAbs against integrins CD11b and CD11c, followed by 24-h coincubation with FH at the monocyte to iDC early differentiation stage.…”
Section: Fh Immunomodulatory Activity Is Mediated Neither By Cr3 or Cmentioning
confidence: 99%